PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) ABAD 21 UNTUK PARA GURU SMA NEGERI & SMK NEGERI DI SURABAYA - Syahria, Nukmatus; Andanty, Ferra Dian; Nabhan, Salim; Setiawan, Rahmat (Faculty of Cultural Studies, Universitas Brawijaya, 2022)
This technical guidance activity was carried out with the aim of socializing the preparation of the21st century Learning Implementation Plan because there are still many biases faced by teachers,especially EFL teachers, related to changes in systems, learning media, and so on, plus, English isincreasingly crucial, so that the role of the EFL teacher must also be adjusted relevantly to the newculture. The data in this study are the results of a questionnaire and the data source is thequestionnaire. The subjects are the participants of the technical guidance who are also EFLteachers and EFL pre-service teachers. The instruments are 5 questions on Strengthening EducationCharacter, 5 questions on Literacy, and 5 questions on HOTS in the Learning Implementation Plan.From the results of the activity, it can be concluded that EFL teachers and EFL pre-service teachersare still not encouraged to strengthen education character but they have realized the importance ofliteracy development and implementation of HOTS in the 21st century Learning ImplementationPlan which is very relevant to technological and digital civilization.